CERITA RAKYAT SUNAN MURIA: PENDEKATAN STRUKTURAL DAN NILAI KARAKTER - Hidar Amaruddin; Yanuar Bayu Isnaeni; Herman J. Waluyo; Sahid Teguh Widodo (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract: This article aims to describe the structure contained in Sunan Muria Folk Literature and describe the character values in Sunan Muria Folk Literature. This research is a qualitative descriptive study. The type of plot used in Sunan Muria Folk Literature in Kudus Regency is a straight or advanced plot. The dominant figure in the Sunan Muria Folk Literature in Kudus Regency is a good human character. More background is used in this folk literature. Sunan Muria Folk Literature in Kudus Regency contains varied suggestions. The character values in this folk literature include religious values, honesty, tolerance, discipline, hard work, independence, democratization, friendship/ communicative, peace, social life, and the value of responsibility. Abstrak: Artikel ini bertujuan untuk mendeskripsikan struktur yang terkandung dalam Sastra Rakyat Sunan Muria dan menguraikan nilai-nilai karakter dalam Sastra Rakyat Sunan Muria. Penelitian ini adalah penelitian deskriptif kualitatif. Jenis plot yang digunakan dalam Sastra Rakyat Sunan Muria di Kabupaten Kudus adalah plot lurus atau maju. Tokoh dominan dalam Sastra Rakyat Sunan Muria di Kabupaten Kudus adalah karakter manusia yang baik. Latar belakang tempat lebih banyak digunakan dalam literatur rakyat ini. Sastra Rakyat Sunan Muria di Kabupaten Kudus berisi saran variatif. Nilai-nilai karakter yang dalam literatur rakyat ini antara lain nilai religi, kejujuran, toleransi, disiplin, kerja keras, kemandirian, demokratisasi, persahabatan/komunikatif, damai, kehidupan sosial, dan nilai tanggung jawab.